Eksplorasi Pengalaman Pengusaha UMKM dalam Pemanfaatan E-commerce untuk Meningkatkan Penjualan dan Keberlangsungan Usaha - Nur Ikhsan, Farid; Mansyuruddin, Wusangkan Maulana; Sijabat, Rauly (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of e-commerce has driven significant changes in the marketing and sales strategies of micro, small, and medium enterprises (MSMEs) in Indonesia. This study aims to explore the experiences of MSME entrepreneurs in utilizing e-commerce to increase sales and maintain business continuity. The research used a qualitative approach using a case study method. Data were obtained through in-depth interviews with MSMEs who utilize e-commerce platforms, particularly marketplaces and live streaming features. Supporting data came from a review of relevant scientific journals. The results show that e-commerce provides tangible benefits for MSMEs, including expanding market reach, increasing sales volume, and fostering direct interactions with consumers, which contribute to increased trust in products. However, entrepreneurs also face various challenges, such as intense price competition, the need for additional personnel for order processing, and the demand for consistency in digital content creation. Overall, e-commerce plays a crucial role in supporting the stability and sustainability of MSME businesses, especially when utilized actively and strategically. This study is expected to provide an empirical overview of e-commerce utilization by MSMEs and serve as a reference for entrepreneurs and future researchers.